PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KARAKTER RELIGIUS PESERTA DIDIK MELALUI KEGIATAN KEAGAMAAN DI SMP RADEN FATAH SIDOMULYO KOTA BATU - Mahfud Muhtadi; Anwar Sa’dullah; Qurroti A’yun (VICRATINA, 2022)
At this time morals or behavior are starting to decline. Making the role of the teacher very important in addition to conveying material, teachers are also required to be able to create a religious atmosphere in the school environment and carry out efforts or strategies that are carried out to help achieve the goals of Islamic education as a whole. The purpose of this study was to determine the religious character, to describe the role of Islamic religious education teachers in shaping the character and supporting and inhibiting factors in carrying out the formation of the religious character of students through religious activities at Raden Fatah Middle School Sidomulyo Batu City. to achieve these objectives the researchers used descriptive qualitative methods. The data collection procedure was carried out using the methods of observation, interviews and documentation. The results of this study are the formation of character in this school goes well and the role of Islamic religious education teachers in shaping the religious character of students through religious activities at Raden Fatah Middle School Sidomulyo Batu City